Tronchuda cabbage (Brassica oleracea L. var. costata DC) seeds: phytochemical characterization and antioxidant potential - Ferreres, Frederico (2007)
Tronchuda cabbage (Brassica oleracea L. var. costata DC) seeds were studied for their chemical composition and antioxidant capacity. Thirteen phenolic compounds were characterized and quantified by reversed-phase HPLC-DAD-MS/MS-ESI and HPLC-DAD, respectively: two sinapoylgentiobiose isomers, three sinapoylglucose isomers, kaempferol-3-(sinapoyl)sophorotrioside-7-glucoside, sinapoylcholine, kaempferol-3,7-diglucoside-40-(sinapoyl)glucoside, three disinapoylgentiobiose isomers, 1,2,20-trisinapoylgentiobiose and 1,2-disinapoylglucose. Seven organic acids (aconitic, citric, ascorbic, malic, quinic, shikimic and fumaric acids) were also identified and quantified by HPLC-UV. The aqueous extract of tronchuda cabbage seeds was investigated for its capacity to act as a scavenger of DPPH- radical and reactive oxygen species (superoxide radical, hydroxyl radical and hypochlorous acid), exhibiting antioxidant capacity in a concentration-dependent manner against all radicals. These results may be attributed to the high content of hydroxycinnamic derivatives and ascorbic acid.